966 The Nonthyroidal Illness Syndrome in Septic Children. (October 2012) - Neamtu, ML; Dobrota, L; Neamtu, MB; Neamtu, CS Berghea; Diac, FS
Abstract : Backgroud: The interpretation of thyroid function tests in the PICU patients can be difficult because thyroid hormone concentrations are affected by nonthyroidial stresses. Most patients fall into sick euthyroid syndrome or nonthyroidal illness syndrome (NTIS). The TH therapy during critical illness remains controversial. Aim: To evaluate the NTIS in septic children. Method: The prospective study conducted on 65 patients admitted in PICU during 12 months period. Inclusion criteria: age > 1 month, admission for critical illness, treatment with corticosteroids, no (documented) history of thyroid pathology. The patients were divided into 2 groups: sepsis and non-sepsis group (dehydration, poisoning, cardiac failure). All patients received corticosteroids. Some of them received in addition dopamine or presented malnutrition. The thyroid hormone assessment was made after the critical diagnosis was established. Results: Sepsis group: 30 patients. Non-sepsis group: 35 patients. NTIS was strongly correlated with sepsis (p<0, 008). Not strongly variation with the addition of dopamine, either for sepsis group (p<0.07) and non-sepsis group (p<0.03). Few patients with malnutrition for both groups, without statistical interpretation. Most frequent variation was observed as "low T3-T4 syndrome" (63%). One single patient (6 months old) was diagnosed as critical hypothyroidism (Sandifer syndrome history), based on clinical complains (severe hypothermia - 32.8 Celsius degrees, bradycardia, altered mental status), less conclusive thyroid hormone tests (high TSH), the only one who received TH therapy. Conclusion: The study confirmed significant correlation between NTIS and sepsis in children (40%). Reassessment of thyroid function should be done away from critical episode.